2021
DOI: 10.1093/bioinformatics/btab562
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolutionary distance predictions contain flexibility information

Abstract: Motivation Co-evolution analysis can be used to accurately predict residue-residue contacts from multiple sequence alignments. The introduction of machine-learning techniques has enabled substantial improvements in precision and a shift from predicting binary contacts to predicting distances between pairs of residues. These developments have significantly improved the accuracy of de novo prediction of static protein structures. With AlphaFold2 lifting the accuracy of some predicted protein mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Related work has studied the search trajectories of fragment replacement methods ( Kandathil et al , 2016 ), or attempted to introduce biological constraints into folding ( de Oliveira et al , 2018 ). Furthermore, recent work has shown that some deep learning predictors can pinpoint flexible residues ( Schwarz et al , 2020 ) or conformational changes ( Del Alamo et al , 2021 ), suggesting that these methods may capture dynamic phenomena reflected in the multiple sequence alignment. In this work, we examine whether protein structure prediction methods are able to reveal anything about a protein’s folding pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Related work has studied the search trajectories of fragment replacement methods ( Kandathil et al , 2016 ), or attempted to introduce biological constraints into folding ( de Oliveira et al , 2018 ). Furthermore, recent work has shown that some deep learning predictors can pinpoint flexible residues ( Schwarz et al , 2020 ) or conformational changes ( Del Alamo et al , 2021 ), suggesting that these methods may capture dynamic phenomena reflected in the multiple sequence alignment. In this work, we examine whether protein structure prediction methods are able to reveal anything about a protein’s folding pathway.…”
Section: Introductionmentioning
confidence: 99%
“… 51 DMPfold 52 , a similar method for general proteins, has been shown to contain flexibility information within inter-residue distance distributions. 53 In principle, DeepAb might provide similar insights into CDR loop flexibility, but further investigation is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a study that found that residues that had differential contacts in conformationally heterogenous proteins had multiple distance peaks in the distance matrix derived from MSAs. 32 Therefore, these regions of uncertainty are targets for conformational switching as well as for direct contact points to consider for alternate conformations.…”
Section: Discussionmentioning
confidence: 99%